2-Deoxy-α-d-arabino-hexopyranose - Hess, David (International Union of Crystallography, 2011)
The title compound, C(6)H(12)O(5), is the α-pyranose form of the reducing aldose 2-deoxy-d-arabino-hexose. The six-membered pyranose ring adopts a (4) C (1) conformation, with the anomeric hydroxy group in axial and the other substituents in equatorial positions. In the crystal, each of the four hydroxy groups acts as an intermolecular hydrogen-bond donor function, resulting in a three-dimensional hydrogen-bonded network.